DIAGNOSTIC PERFORMANCE OF ULTRASONOMETER FOR EVALUATION OF OSTEOPOROSIS IN POSTMENOPAUSAL WOMEN - UARATANAWONG, Somsri; UARATANAWONG, Somchai; BOONYAVISUT, Varodom (The ASEAN Journal of Radiology, 2023)
Objects: To evaluate the diagnostic performance of quantitative ultrasound (QUS) Study design: A diagnostic test (Cross-sectional descriptive study) Methods: 324 postmenopausal women were evaluated for bone mineral density (BMD) at the lumbar spine and femoral neck by dual energy X-ray absorptiometry (DEXA) at Nuclear Medicine Division, Bangkok Metropolitan Administration and Vajira Hospital from January 2003-November 2004. BMDs were interpreted as osteoporosis by WHO criteria. The speed of sound (SOS) was also measured at the distal third of radius by quantitative ultrasound (QUS). Results: The prevalence of osteoporosis in our study was 30.8%, sensitivity, specificity, positive predictive value, negative predictive value and positive likelihood ratio were 62%, 91.5%, 76.5%, 84.4% and 7 respectively. Conclusion: SOS measurement at the distal third of radius by QUS had moderate sensitivity, but had high specificity when use DEXA as a gold standard and use WHO T-score as a reference. The highly specific test has been useful to confirm a diagnosis that has been suggested JAN. - APR. 2005. Volume XI Number! by other clinical data.